Acute Inflammatory Responses To Three Different Isokinetic Bench Press Loading Protocols - Koski, Max (2021)
Introduction: Exercise disturbs the homeostasis in the body and induces a transient inflammatory response leading to an acute increase in acute phase proteins, cytokines and enzymes, which can be classified as an acute inflammatory response to exercising. The purpose of this study was to evaluate the effects of an isokinetic bench press protocols consisting of eccentric-only (ECC), concentric-only (CON) and combined (COMB) concentric-eccentric muscle actions on the acute inflammatory markers interleukin-6 (IL-6), C-reactive protein (CRP) and muscle damage marker creatine-kinase (CK).